Evaluation of Size of Ventricles of Human Brain using Magnetic Resonance Imaging Technique - Poudel, Deewakar; Lamichhane, Hari Prasad; Paudel, Sharma; Chand, Ram Bahadur (Journal of Institute of Science and Technology, 2015)
The prospective cross-sectional study of human brain was conducted to establish the range of size of ventricular system in normal human brain of Nepalese population (irrespective of race) by using magnetic resonance imaging (MRI) at Institute of Medicine, Department of Radiology and Imaging, Tribhuvan University Teaching Hospital (TUTH) on 150 subjects (75 male and 75 female) of age between 10 - 80 years with 0.3 Tesla static magnetic field. The bifrontal diameter, bihemispheric diameter, frontal horn ratio, transverse dimension of third ventricle, anterior - posterior dimension and width of fourth ventricle were observed to be 32.7 mm and 31.0 mm, 105.1 mm and 101.2 mm, 0.31 and 0.31, 4.7 mm and 4.4 mm, 9.9 mm and 9.4 mm, 12.3 mm and 11.7 mm in case of male and female respectively with overall average of 31.9 mm, 103.1 mm, 0.31, 4.6 mm, 9.7 mm, and 12.0 mm respectively. The measurement of ventricular dimension was observed to be statistically significant between male and female except transverse dimension of third ventricle and was greater in male than in female in all cases. Journal of Institute of Science and Technology, 2015, 20(1): 6-14